Réflexions sur le crime d’indignité nationale et la peine de dégradation nationale - Sébastien Le Gal (Cahiers Jean Moulin)
National unworthiness (“indignité nationale”) was first introduced into French Law in an ordinance passed on August 26, 1944 and applied to any French national convicted of collaborating with Germany or having a behaviour detrimental to national unity. It carries a sentence called national stripping of rank (“degradation nationale”) that was largely handed down after the liberation. The terrorist attack committed on January 7, 2015 re-emphasised this penal provision. However, legal and political considerations lead to the conviction that the sentence of national stripping of rank would be both unnecessary and inefficient against the terrorist threat the country faces today.